Phylogenetic analyses of termite post‐embryonic sequences illuminate caste and developmental pathway evolution. Issue 2 (4th March 2013) - Legendre, Frédéric; Whiting, Michael F.; Grandcolas, Philippe
SUMMARY Termites are highly eusocial insects with a caste polyphenism (i.e., discontinuous morphological differences between castes) and elaborated behaviors. While the developmental pathways leading to caste occurrence are well‐known in many species, the evolutionary origin of these pathways is still obscure. Recent molecular phylogenetic studies suggest multiple independent origins of sterile castes in termites, reviving a 30 years old debate. We demonstrate here that diploid sterile castes ("true" workers) evolved several times independently in this group and that this caste was lost at least once in a lineage with developmentally more flexible workers called pseudergates or "false" workers. We also infer that flexibility in post‐embryonic development was acquired multiple times independently during termite evolution. We suggest that focusing on detailed developmental pathways in phylogenetic analyses is essential for elucidating the origin of caste polyphenism in termites.